Spatial distribution of halophytes in the Mondego salt marsh and plant responses to environmental conditions - Castro, Paula; Freitas, Helena (Ecological Questions, 2011)
We propose to analyze the spatial distribution of halophytes in the salt marsh of the Mondego estuary in order to understand how environmental conditions affect their distribution patterns. Furthermore we discuss the responses of these species to human activities in this ecosystem and the consequent increase in nutrient loading.